Paper cup and paper bowl design to support economic resilience through the green economy concept - Fitriyani, Zenita Afifah (Journal of Economics Research and Policy Studies, 2025)
Pujasera Embong Tengah is one of the culinary places that has not implemented the green economy concept because the problems faced are that business actors in Pujasera Embong Tengah feel that environmentally friendly packaging is very complicated, stock availability is still difficult, costs are more expensive, and do not understand how to design packaging, so the packaging used still uses plastic that is not environmentally friendly and less attractive. The purpose of this study is to design paper cups and paper bowls to support the concept of green economy. The method used in the study is descriptive qualitative with a field study approach with sampling using the purposive sampling method. Respondents in the study were sellers and consumers. The image was designed using the AutoCAD application. The results of the study showed that the design of paper cups and paper bowls was easy to communicate, creative, different from competitors, and acceptable to consumers. This study examines the use of paper cups and paper bowls to support the concept of green economy. The findings of this study can provide important information to help the economic resilience of business actors, as well as provide insight for further research development. This study hopes that Pujasera Embong Tengah can change its packaging from plastic to environmentally friendly packaging with an attractive design so that economic resilience is maintained.